Extending the developmental origins of disease model: Impact of preconception stress exposure on offspring neurodevelopment. Issue 7 (24th August 2018) - Keenan, Kate; Hipwell, Alison E.; Class, Quetzal A.; Mbayiwa, Kimberley
Abstract: The concept of the developmental origins of health and disease via prenatal programming has informed many etiologic models of health and development. Extensive experimental research in non‐human animal models has revealed the impact of in utero exposure to stress on fetal development and neurodevelopment later in life. Stress exposure, however, is unlikely to occur de novo following conception, and pregnancy health is not independent of the health of the system prior to conception. For these reasons, the preconception period is emerging as an important new focus for research on adverse birth outcomes and offspring neurodevelopment. In this review, we summarize the existing evidence for the role of preconception stress exposure on pregnancy health and offspring neurodevelopment across species and discuss the implications of this model for addressing health disparities in obstetrics and offspring outcomes.